The Mediating Roles of Customer Trust and Satisfaction in E-Service Quality and the Repurchase Intention Relationship - Muhammad Iffan; M. Yani Syafei; Nguyen Duy Cuong (Australasian Accounting, Business and Finance Journal, 2024)
The rapid growth of information technology and the internet has changed how the company runs its business. In an increasingly competitive business environment, gaining and increasing market share is a priority for companies in the E-Commerce industry. The study aims to determine the impact of E-Service Quality on Repurchase Intention, mediated by Customer Trust and Customer Satisfaction on E-Commerce users. The data is processed using a quantitative approach using the SEM-PLS method. The validity and reliability tests are first performed to determine the validity of the data, followed by the analysis of Structural Equation Modelling to determine the direct and indirect effect between research variables. Research results show that E-Service Quality significantly affects Customer Trust and Customer Satisfaction. In addition, Customer Trust and Customer Satisfaction significantly affect Repurchase Intention. Furthermore, E-Service Quality does not directly have a significant effect on Repurchase Intention. However, E-Service Quality indirectly affects Repurchase Intention through Customer Trust and Customer Satisfaction. Based on the research results, E-Commerce users make online repurchases not only based on the quality of the service received but also on the consumer's trust and satisfaction generated by the product or brand offered, which can significantly increase consumer repurchasing.
Keywords: E-Service Quality; Customer Trust; Customer Satisfaction; Repurchase Intention; E-Commerce.